2021
DOI: 10.3390/cancers13071524
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Techniques for Prostate Cancer Detection through Dual-Channel Tissue Feature Engineering

Abstract: The optimal diagnostic and treatment strategies for prostate cancer (PCa) are constantly changing. Given the importance of accurate diagnosis, texture analysis of stained prostate tissues is important for automatic PCa detection. We used artificial intelligence (AI) techniques to classify dual-channel tissue features extracted from Hematoxylin and Eosin (H&E) tissue images, respectively. Tissue feature engineering was performed to extract first-order statistic (FOS)-based textural features from each staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In recent years, successful applications of CNNs in various fields have been reported. In the field of medical imaging, CNN architectures have shown efficient results similar to or better than those of human experts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In this study, we proved that a CNN architecture can accurately detect mandibular third molars and predict paresthesia before third molar extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, successful applications of CNNs in various fields have been reported. In the field of medical imaging, CNN architectures have shown efficient results similar to or better than those of human experts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In this study, we proved that a CNN architecture can accurately detect mandibular third molars and predict paresthesia before third molar extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning has developed rapidly in recent years, making it possible to automatically extract information in the medical field, from diagnosis using medical imaging to analysis of activity and emotional patterns [ 1 , 2 , 3 ]. The deep convolutional neural network (CNN), a type of deep learning, has been widely applied to medical images due to its high performance in detection, classification, quantification, and segmentation [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supervised learning models are analyzed in conjunction with outcome variables to establish a mathematical representation between the selected characteristics and the target variables, a widely utilized method in radiomic analysis. Support vector machine (SVM) is a commonly employed promising discriminative classification technique and is a typical practice to introduce multiple classification models for profiling to achieve better performance (24,(71)(72)(73). For instance, Kim et al (71) showed that SVM, logistic regression (LR), bagging tree, boosting tree, and dual-channel bidirectional long and short-term memory network performed well for prostate cancer identification on tissue images.…”
Section: Model Construction and Classification/ Predictivementioning
confidence: 99%
“…Support vector machine (SVM) is a commonly employed promising discriminative classification technique and is a typical practice to introduce multiple classification models for profiling to achieve better performance (24,(71)(72)(73). For instance, Kim et al (71) showed that SVM, logistic regression (LR), bagging tree, boosting tree, and dual-channel bidirectional long and short-term memory network performed well for prostate cancer identification on tissue images. Many other supervised classifiers exhibit favorable learning abilities such as the least absolute shrinkage and selection operator-LR (74), multivariate Cox proportional hazards regression models (59), decision trees (75), and random forest (51).…”
Section: Model Construction and Classification/ Predictivementioning
confidence: 99%
“…The aim of this paper was to differentiate the tumor types (meningioma, glioma, and pituitary) by performing binary and multiclass classification using AI techniques. In this study, we developed a long short-term memory (LSTM) [8] neural network model and used ML classifiers, namely support vector machine (SVM), k-nearest neighbor (KNN), logistic regression (LR), random forest (RF), and linear discriminant analysis (LDA), to perform multiclass and binary classification. In general, LSTM is used and well suited in classifying and making predictions based on convolutional neural network (CNN)-extracted features [7] or time-series data.…”
mentioning
confidence: 99%